Formation of inclusion complex of curcumin and tetrahydrocurcumin prevents angiogenesis by inhibiting VEGF activity: an in-silico study - Dewi, Firli Rahmah Primula; Tambunan, Ulie Vianissa Dwiutami; Bari, Putri Amatul; Farid, Muhammad Ardiansyah; Anjani, Nadira Aisha; Wahyuningsih, Sri Puji Astuti; Saik, Amy Yi Hsan; Yong, Yoke Keong; Lim, Vuanghao; Tan, Wen Nee; Alshawsh, Mohammed Abdullah Mahdi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Curcumin and tetrahydrocurcumin (THC) are known for their anticancer properties, but limited solubility in water hinders their effectiveness against cancer. In this study, we conducted an in silico exploration of β-cyclodextrin’s potential to form inclusion complexes with curcumin or THC. The aim of this study was to assess the potential of curcumin and THC inclusion complexes to inhibit vascular endothelial growth factor (VEGF) signaling pathway, a key element in carcinogenesis. The in silico analysis involved multiple stages, such as bioactive compound preparation, biological activity prediction, 3D structure retrieval of VEGF and VEGFR, protein-ligand docking, and visualization. The results of the study demonstrated that both the curcumin- and THC-inclusion complexes exhibit a lower requirement for binding free energy to interact with VEGFR compared to curcumin or THC molecules alone. When VEGFR binds with curcumin, the curcumin-inclusion complex, or the THC-inclusion complex before interacting with VEGF, there is a notable increase in the binding free energy for the VEGF-VEGFR interaction. Specifically, the presence of THC-inclusion complex demonstrates the highest binding free energy for the VEGF-VEGFR interaction. The molecular dynamic simulation study shows that when VEGFR binds with curcumin, curcumin-inclusion complex, or THC-inclusion complex, the fluctuation of amino acid residues in VEGFR decreases compared to the VEGFR protein structure before binding with these molecules. In conclusion, this study suggests that the formation of inclusion complexes holds considerable promise for enhancing the anticancer potential of curcumin and THC by augmenting their anti-angiogenic activity. © 2024 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.